The Characterization of Black-streaked Heartwood in Teak: Inter-tree Variation - Ganis Lukmandaru; Tatsuya Ashitani; Koetsu Takahashi (Wood Research Journal, 2014)
The objective of  this  study was to  investigate the  variation in the  color and chemical characteristics of  black-streaked heartwood of teak and explore the relationship of these chemical properties with the  degree of blackening. The samples used were outer heartwood parts from  11  trees with  black streaks both  thin  and thick and 7  trees with  normal heartwoods for comparison.  The colorimetric  analysis in  CIEL*a*b*  system was used to  determine  the  brightness  values (L*)  of  black- streaked heartwood of teak ranging from  40~49 and a thick portion produced appreciably higher average values of extractive contents including  n-hexane,  ethyl acetate, and total  extractive  content as well as tectoquinone contents and pH values but lower squalene content compared to those in normal wood. The degree of blackening in the  black-streaked  heartwood was highly correlated to its extractive contents, especially the  ethyl acetate soluble extractive content (r = −0.94) while moderate correlations  were measured  between  the  brightness  index  and  tectoquinone content (negative)  and squalene (positive). Moreover, no  significant difference was found in the  ash and individual inorganic elements contents between the  group. The increase  in  pH   values  was observed  to  have  corresponded with  a decrease  in  brightness  (r  = -0.75).  Therefore,  the blackening was assumed to be  due to the  polymerization of quinones in weakly acidic conditions